Feline characteristics in English and Malay feline proverbs: a conceptual metaphor approach / Siti Mukhlisa Mohamad Khairul Adilah and Marlina Jamal - Mohamad Khairul Adilah, Siti Mukhlisa; Jamal, Marlina (Universiti Teknologi MARA, Kedah, 2021)
The study deals with the examination of feline characteristics in selected English and Malay proverbs through utilizing a conceptual metaphor theory. The main objective is to investigate the difference in terms of the representation of feline characteristics in Malay and English proverbs. A qualitative analysis was conducted on 16 English and 86 Malay feline proverbs by integrating conceptual metaphor approach by Lakoff and Johnson (1980). Findings revealed that there are fewer feline proverbs in English as compared to Malay, and that dominant feline lineage such as tigers is projected to be powerful, while the domestic feline such as cats is associated with timidity. This study brings to surface the relationship between human, animals and surroundings in shaping the representations of meanings by both societies, which would be beneficial for the comprehension process among the language learners.